Relationship between initial symptoms and the prognosis, sex, and demographic area of patients with COVID-19 - Oliván-Blázquez, Bárbara; Bartolomé-Moreno, Cruz; Gericó-Aseguinolaza, Junkal; Méndez-López, Fátima; Lerma-Irureta, David; Lamiquiz-Moneo, Itziar; Fernández-Martínez, Selene; Magallón-Botaya, Rosa (Frontiers in Medicine, 2022)
Background A method of determining the initial symptoms and main prognostic identifiers for COVID-19 can be a key tool for physicians, especially primary care physicians. Therefore, the objective of this study was to examine the prognosis of patients with COVID-19 from two different demographic regions according to baseline and main symptoms, age, and sex. Methods All individuals selected from both urban and rural health centers were over 18 years of age, had COVID-19 before 2 March 2021, and were followed up with a primary care physician. All patients included in this study were recruited in terms of sex, age at the time of infection, type of contact, baseline symptoms, primary and secondary symptomatology, emergency assistance, hospitalization, intensive care unit (ICU) admission, and death. Results A total of 219 and 214 subjects were recruited from rural and urban health centers, respectively. Subjects with COVID-19 from rural areas were significantly older in age, with a higher proportion of men, and had significantly lower baseline and main symptoms than those from urban areas. In addition, the presence of both fever and dyspnea as the initial or main symptom is significantly associated with emergency assistance, hospitalization, and death, regardless of sex, age, and demographic area. This type of illness was reported to be significantly less frequent in the rural population than in the urban population. Conclusion The presence of both fever and dyspnea as both initial and main symptoms is a poor prognostic factor for COVID-19, regardless of age, sex, and demographic areas. In addition, women reported lower levels of fever and dyspnea, requiring minimal emergency assistance and fewer hospitalization, and a lower rate of mortality than men. During a COVID-19 infection follow-up, subjects in rural areas seem to have less access to medical care than those in urban areas.